Stop-go, fast-slow - McLenighan, Valjean; Fiddle, Margrit (Chicago : Childrens Press, 1982)
A short poem emphasizing the concept of opposites. Includes word list.
1.5.
2.1
K-3
P-2.
Keywords: English language -- Synonyms and antonyms -- Juvenile literature; English language -- Synonyms and antonyms; English language -- Synonyms and antonyms